Kolesteatom cerrahisinde supratubal reses tutulumunun değerlendirilmesi - (:unkn) unknown (My University, 2000)
Amaç: Kolesteatom cerrahisinde supratubal reses (STR) tutulumunu değerlendirmek. Hastalar ve Yöntemler: Kliniğimizde ameliyat ettiğimiz kolesteatomlu veya yassı epitelli 258 kronik otitis media olgusu ve kolesteatoma bağlı gelişen 12 fasyal paralizi olgusunda STR tutulumu retrospektif olarak incelendi. Olguların ameliyat öncesi radyolojik bulguları (Schüller-Town ve/veya bilgisayarlı tomografi) ve intraoperatif bulgular değerlendirildi. Bulgular: Kolesteatomlu veya yassı epitelli kronik otitis media olgularının %20'sinde (n=52) ve kolesteatoma bağlı gelişen fasyal paralizili olguların %50'sinde (n=6) STR tutulumu izlendi. Sonuç: Rezidüel kolesteatom ve kolesteatom rekürensini önlemek için STR anatomisinin ve bu bölgeye cerrahi yaklaşımın anlaşılması gerekmektedir.

Objectives: To evaluate involvement of the supratubal recess (STR) in cholesteatoma surgery. Patients and Methods: Involvement of STR was sought in 258 patients who underwent surgery for chronic otitis media with cholesteatoma or squamous epithelium and in 12 patients who developed facial paralysis secondary to cholesteatoma. Preoperative radiological findings (Schuller-Town and/or computed tomography) and intraoperative findings were evaluated. Results: Involvement of STR was detected in 20% (n=52) of patients with cholesteatoma or squamous epithelium and in 50% (n=6) of patients who underwent facial decompression because of cholesteatoma. Conclusion: In order to avoid residual cholesteatoma or cholesteatoma recurrence, the anatomy of STR and its surgical implications should be appreciated.
Evaluation of the supratubal recess involvement in cholesteatoma surgery
Keywords: Mikroskopi; Tıbbi Araştırmalar Deneysel; Kulak, Burun, Boğaz